An Architecture for Fog Computing Emulation - Coutinho, Antonio A. T. R.; Greve, Fabíola; Prazeres, Cássio (Anais do Workshop em Clouds e Aplicações (WCGA), 2017)
Fog computing is an emergent paradigm that integrates cloud computing services into the network on a widely distributed level. It extends cloud capabilities near data sources to overcome limitations of cloud-based IoT platforms such as mobility, location awareness and low latency. In spite of its increasing importance, there exist no readily available fog computing platforms which can help researchers to design and test real world fog applications. To this purpose, simulators and testbeds are adapted to enable the investigation of fog solutions. This paper presents a framework architecture to create fog virtualized environments. Its design meets the requirements of low cost, flexible setup and compatibility with real world technologies. Unlike current approaches, the proposed architecture allows for the testing of fog components with third-party systems through standard interfaces. A scheme to observe the behavior of the environment by monitoring network flow is provided. In addition, future developments and research directions are discussed.